L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

Ep.1 - Violences invisibles - Les violences psychologiques et économiques - VIOLENCE QUE FAIRE (2021)
Les violences psychologiques et économiques au sein du couple, qu'est-ce que c'est ? En quoi sont-elles différentes d’un conflit ordinaire ? Comment s’installent-elles ? Quelles en sont les conséquences et comment s’en sortir ? Mêlant l'analyse du Docteur Emmanuel Escard, Médecin adjoint responsable de l'Unité Interdisciplinaire de Médecine et de Prévention de la Violence (UIMPV) et de nombreux extraits de témoignages d'anciennes victimes, Poussière apporte un éclairage sur ces questions. Vous ou l'un-e de vos proches êtes concerné-e-s par les violences au sein du couple ? Vous n'êtes pas sûr-e ? Posez votre question sur www.violencequefaire.ch et un-e professionnel-le vous répondra dans un délai de trois jours ouvrables. Un podcast de VIOLENCE QUE FAIRE Réalisation: Julia Guglielmetti Graphisme : Julia Guglielmetti Musique : Pylone (Valentin Perroud) - Bloom
Keywords: approches et analyses; cours; discipline; médecine; pol5480; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences; thématiques; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual health studies in gay and lesbian people: A critical review of the literature - Mijas, Magdalena; Grabski, Bartosz; Blukacz, Mateusz; Davies, London, UK, Dominic Pink Therapy (The Journal of Sexual Medicine, 2021)
Arrière-plan Le sujet de la santé sexuelle des gays et des lesbiennes semble être très peu étudié, au moins en partie en raison des limites générales inhérentes aux études sur la sexualité ainsi que des préjugés hétéronormatifs et des difficultés à atteindre ces populations. But Examiner de manière critique les études sur la santé sexuelle des gais et des lesbiennes afin d'identifier les lacunes et les préjugés existants dans la portée et la construction générale des recherches publiées. Méthodes L'ensemble de données comprenait 556 articles évalués par des pairs et identifiés grâce à la recherche Medline. Les caractéristiques clés des études ont été extraites selon le livre de codes développé pour cette étude et analysées de manière descriptive. Résultats Les résultats comprenaient : la méthodologie de recherche, la conception de l’étude, l’échantillonnage, le sujet de recherche et l’inclusion de la diversité dans les populations étudiées. Résultats La majorité des études étaient quantitatives (70,5 %), transversales (83,6 %) et utilisaient un échantillonnage de commodité (83,2 %). La plupart des articles portaient sur les comportements à risque en matière de VIH/IST, les vulnérabilités et la gestion des risques (26,3 %). Le sujet le moins souvent abordé concernait la fonction sexuelle des participants gais et lesbiennes plus âgés (0,5 %). Plus de 68 % des articles s'appuyaient sur des échantillons masculins et les études portant sur des échantillons exclusivement féminins en représentaient moins de 13 %. La plupart des études n'ont pas recruté de groupe d'âge spécifique (77,7 %) et incluaient des informations sur l'origine ethnique des participants à l'étude (62 %). Les informations sur l'éducation (58,7 %) ou d'autres indicateurs du statut socio-économique (52,8 %) étaient moins souvent déclarées. Traduction clinique Les limites méthodologiques des conceptions d'étude actuelles, des procédures d'échantillonnage et de la composition des échantillons, ainsi que de nombreuses zones d'omission limitent l'utilité clinique des recherches existantes. Points forts et Limites Cette étude offre un aperçu critique des défis les plus importants associés aux études sur la santé sexuelle des gais et des lesbiennes. La recherche dans la base de données Medline uniquement, l'inclusion exclusive d'articles rédigés en anglais et la portée limitée (sexualité gay et lesbienne uniquement) de la revue constituent les limites les plus importantes. Conclusions La santé sexuelle des gays et des lesbiennes est un domaine peu étudié, caractérisé par une concentration principale sur le VIH/IST et un manque de recherche de meilleure qualité incluant diverses sous-populations.
Keywords: approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; médecine; personnes gay; personnes lesbiennes; ressource en ligne; revue de la littérature; santé; santé sexuelle; sciences; systèmes d'oppressions; thématiques

Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Number: 5
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis

Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Section: 246 pages : tableaux, graphiques en couleur ; 28 cm
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

The vulva: Physiology and clinical management - Farage, Miranda A.; Maibach, Howard I. (CRC Press, 2017)
Compilation unique d'expertise sur l'anatomie, la physiologie, les questions cliniques et la recherche actuelle, ce manuel analyse la diversité des présentations en fonction de l'âge, de l'origine ethnique, des symptômes, des troubles, des diagnostics et de la toxicité. La deuxième édition de cette ressource essentielle pour toute personne prenant soin de patientes a été doublée pour inclure des chapitres supplémentaires. Tous les médecins, qu'ils soient dermatologues ou gynécologues, ainsi que ceux qui recherchent les preuves scientifiques et les symptômes, bénéficieront de l'expérience des contributeurs et éditeurs experts réunis ici.
Keywords: 2000 à aujourd'hui; corps; dermatologie; discipline; gynécologie; médecine; projet charge mentale; périodes historiques; santé; santé menstruelle; santé reproductive; santé sexuelle; sciences; sexualité; sexualité des femmes*; thématiques

Sex and gender considerations in transplant research: A scoping review - Laprise, Claudie; Cole, Katherine; Sridhar, Vikas Srinivasan; Marenah, Tida; Crimi, Cassandra; West, Lori; Foster, Bethany J.; Pilote, Louise; Sapir-Pichhadze, Ruth (Transplantation, 2017)
Background Despite the growing appreciation of the importance of sex and gender considerations in transplantation research, there is currently no framework or good practice guidelines for the appropriate handling of sex and gender issues in human allotransplantation research. Methods We will conduct a scoping review to synthesize the evidence on how matters of sex and gender have been handled in human allotransplantation research. We will survey the literature discussing sex and gender in relation to transplantation, including adult and pediatric patients, hematopoietic and solid organ transplant recipients as well as organ donors. We will search MEDLINE and Embase for literature discussing sex and gender in relation to transplantation. Two reviewers will independently evaluate the eligibility of all identified titles and abstracts for inclusion in the full text review, as well as data extraction. Descriptive data and information on how sex and gender have been considered in human transplantation research will be reported. Discussion This scoping review will be an important stepping stone towards the development of good practice guidelines on study design and analysis considerations when handling sex and gender issues in human transplantation research. This scoping review can also help identify methodological issues that restrict the translation of transplantation research findings into clinical practice related to underestimation of sex/gender differences. This review will ultimately identify major gaps, inform donor-recipient selection, guide personalized interventions, and prioritize research recommendations in human transplantation research. Electronic supplementary material The online version of this article (10.1186/s13643-017-0578-4) contains supplementary material, which is available to authorized users. Keywords: Sex, Gender, Transplantation, Scoping review
Keywords: 2000 à aujourd'hui; corps; discipline; médecine; projet charge mentale; périodes historiques; ressource en ligne; santé; sciences; thématiques; transplantation

À qui appartient-il de déterminer les modes d’intervention auprès des personnes intersexuées ? - Bastien Charlebois, Janik (Nouvelles pratiques sociales, 2016)
Les personnes intersex(ué)es sont au coeur de tensions dans l’orientation des pratiques médicales sur leur corps et la détermination de leur « propre bien ». La volonté d’autodétermination relayée par les acteurs sociaux politisés et les critiques qu’ils formulent à l’endroit des médecins se heurtent au déficit de crédibilité que celle-ci leur accorde. En isolant certains des motifs les plus solides du maintien de la primauté médicale sur l’orientation des pratiques, nous relevons les arguments développés par la communauté intersexe pour y répondre. Cette réflexion est menée à partir des perspectives philosophiques de Young sur l’autodétermination et du concept d’injustice épistémique de Fricker.
http://www.erudit.org/fr/revues/nps/2016-v28-n1-nps02990/1039174ar/
Keywords: approches et analyses; autodétermination; corps; cours; discipline; fem1000; histoire et politique; identités LGBTQIA2+; lit4700; militance; médecine; personnes intersexes; point de vue situé; premier cycle; ressource en ligne; sciences; thématiques

Prendre en compte le sexe et le genre dans le choix des situations à analyser : un enjeu pour l’intervention ergonomique - Laberge, Marie; Caroly, Sandrine (Perspectives interdisciplinaires sur le travail et la santé, 2016)
Le sexe/genre (s/g) doit être pris en compte dans le domaine de la santé au travail, puisque les hommes et les femmes n’occupent pas les mêmes emplois et ne sont pas exposés de la même façon aux risques de santé et sécurité au travail (SST). Cet article propose une réflexion sur les manières de considérer le s/g dans l’intervention ergonomique, en particulier lors des investigations préliminaires. Deux exemples issus d’interventions réalisées en France et au Québec sont présentés. Le premier exemple porte sur l’activité des médecins du travail dans la prévention des troubles musculosquelettiques (TMS). Le second traite du développement et de l’implantation d’une formation portant sur la SST. Dans les deux cas, ces questions portées par les ergonomes chercheuses ont permis de transformer la compréhension des dimensions liées aux parcours de santé, de travail et de vie personnelle pour que la prévention des lésions tienne compte des particularités des hommes et des femmes.
Keywords: amériques; discipline; ergonomie; europe; france; médecine; projet charge mentale; québec; ressource en ligne; régions géographiques; santé; santé au travail; sciences; thématiques; travail

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Gender matters in biological research and medical practice ∗ - Schiebinger, Londa; Stefanick, Marcia L. (Journal of the American College of Cardiology, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; corps; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; santé; sciences; thématiques

Why sex and gender matter in implementation research - Tannenbaum, Cara; Greaves, Lorraine; Graham, Ian D. (BMC Medical Research Methodology, 2016)
Arrière-plan Les organismes de financement de la recherche en santé et les rédacteurs de revues scientifiques ont récemment intensifié leurs efforts pour accroître la prise en compte des questions de sexe et de genre dans la conception, la conduite et la communication des études afin de garantir que les résultats de la recherche s’appliquent à tous. Cependant, l’examen de la littérature sur la recherche sur la mise en œuvre révèle que l’attention portée au sexe et au genre n’a pas encore infiltré les méthodes de recherche dans ce domaine. Discussion Les raisons pour lesquelles le sexe et le genre sont systématiquement pris en compte dans la recherche sur la mise en œuvre sont multiples. Le sexe et le genre sont importants dans la prise de décision, la communication, l’engagement des parties prenantes et les préférences pour l’adoption des interventions. Les rôles de genre, l’identité de genre, les relations de genre et le genre institutionnalisé influencent la manière dont une stratégie de mise en œuvre fonctionne, pour qui, dans quelles circonstances et pourquoi. De nouvelles preuves montrent que les théories des programmes peuvent fonctionner différemment au sein et entre les sexes, les genres et d’autres caractéristiques intersectionnelles dans diverses circonstances. En outre, sans une étude appropriée, les stratégies de mise en œuvre peuvent exploiter ou ignorer par inadvertance, plutôt que de transformer la réflexion sur le sexe et les facteurs liés au genre. Des techniques sont décrites pour mesurer et analyser le sexe et le genre dans la recherche sur la mise en œuvre en utilisant des méthodes à la fois quantitatives et qualitatives. Résumé Le présent article décrit l’application de méthodes d’intégration du sexe et du genre dans la recherche sur la mise en œuvre. Poser systématiquement des questions critiques sur le sexe et le genre conduira probablement à la découverte de résultats positifs, ainsi que de conséquences imprévues. Le résultat a le potentiel de renforcer à la fois la pratique et la science de la mise en œuvre, d’améliorer les résultats en matière de santé et de réduire les inégalités entre les sexes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; régions géographiques; santé; santé publique; sciences; thématiques; transfert des connaissances

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Trauma and recovery: The aftermath of violence, from domestic abuse to political terror - Herman, Judith Lewis (Basic Books, 2015)
Lorsque Trauma and Recovery a été publié pour la première fois en 1992, il a été salué comme un travail révolutionnaire. Au cours des années intermédiaires, le volume de Herman a changé la façon dont nous pensons et traitons les événements traumatisants et les victimes de traumatismes. Dans une nouvelle postface, Herman raconte l'incroyable réponse que le livre a suscitée et explique comment les problèmes entourant le sujet ont changé au sein de la communauté clinique et de la culture en général. Traumatisme et récupération apporte un nouveau niveau de compréhension à un ensemble de problèmes généralement considérés individuellement. Herman s'appuie sur ses propres recherches de pointe sur la violence domestique ainsi que sur la vaste littérature des vétérans de combat et des victimes de la terreur politique, pour montrer les parallèles entre les terrorismes privés tels que le viol et les traumatismes publics tels que le terrorisme. Le livre met l'expérience individuelle dans un cadre politique plus large, arguant que le traumatisme psychologique ne peut être compris que dans un contexte social. Méticuleusement documenté et utilisant fréquemment les propres mots des victimes ainsi que ceux des œuvres littéraires classiques et des journaux de prison, Trauma and Recovery est un travail puissant qui continuera à avoir un impact profond sur notre pensée
Keywords: abus sexuels; cours; discipline; enfance; médecine; psychiatrie; terrorisme; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social

Butch/femme, F2M, pregnant man, tranny-boi: Gender issues in the lesbian community - Herbert, Sandra (Journal of Gay and Lesbian Mental Health, 2010)
The author discusses issues pertaining to transgender women and girls. Women identifying as male or transitioning to becoming male are often ignored in the scientific and lay literature on transgender people. The many newer terms for transgender women and girls are discussed, as well as new ways for transgender girls to express their identities. The importance of family and community supports is discussed, and common issues that young transgender people bring into mental health treatment are elucidated.
Keywords: amériques; discipline; identités LGBTQIA2+; médecine; personnes trans*; ressource en ligne; régions géographiques; santé; sciences; thématiques; états-unis

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

L’impact des violences structurelle et conjugale en contexte migratoire: Perceptions d’intervenants pour le contrer - Rojas-Viger, Celia (Nouvelles pratiques sociales, 2008)
Résumé Le Canada et le Québec, sociétés pluriethniques, possèdent des politiques et des programmes de promotion et de prévention pour contrer les violences faites aux femmes, mais reconnaissent que le défi est de taille dans le contexte migratoire. Les immigrantes, confrontées à la violence conjugale, ne disposent souvent pas d’accessibilité culturelle aux services sociaux et de santé ou n’obtiennent pas de réponse adéquate à leurs besoins. Toutefois, certains organismes ont des projets pour leur venir en aide mais ils ne sont pas systématiques. L’article présente les résultats d’une recherche exploratoire, avec approche ethnologique, qui documente la perception de 10 intervenants d’organismes communautaires et institutionnels concernant leurs activités dans le domaine et leur préoccupation pour la promotion et la prévention primaire, même si leurs pratiques concrètes sont surtout centrées sur la prévention secondaire. Maints empêchements les limitent, mais leurs perceptions des réponses promotionnelles et préventives mettent en lumière l’impact de la violence structurelle et de la violence conjugale et orientent les perspectives de renouvellement des pratiques d’intervention sociosanitaire en matière de violence conjugale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; médecine; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; systèmes d'oppressions; thématiques; trs3500; violence systémique; violences; violences conjugales

La procréation assistée, comment y voir clair? - Fédération du Québec pour le Planning des naissances (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; discipline; femmes*; maternité; médecine; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; sciences; thématiques

Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Sur la noblesse et l'excellence du sexe féminin, de sa préminence sur l'autre sexe - Agrippa de Nettesheim, Henir Corneille (De l' indécence aux hommes d'accoucher les femmes et De l' obligation aux mères de nourrir leurs enfants suivi de S'il est des signes qui assurent de la puissance des hommes, autant que le font ceux qui répondent de la sagesse des filles, 1990)
Le texte d'Henri Corneille Agrippa, Discours abrégé sur la noblesse et l'excellence du sexe féminin, de sa prééminence sur l'autre sexe, n'est pas seulement une contribution importante à l'histoire du discours sur la différence des sexes : pris hors contexte, il constitue aussi une divertissante démonstration par l'absurde de l'inadéquation de l'analyse des rapports de sexe en termes de déduction par rapport à des attributs (imaginaires ou réels) qui en constitueraient l'essence. Réédition d'après l'éd. de 1744, dont l'orthographe et la ponctuation ont été modernisés (indication de la préf. de 1990).
Première édition 1537 Donné en lecture cours FEM1000: p.28-31;98-109;111;134-137
Keywords: 1700-1799; approches et analyses; cours; discipline; europe; fem1000; france; histoire; histoire des femmes*; maternité; médecine; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexes; thématiques

"Je me suis fait la guerre", ou comment être un "bon arabe" - Radiofrance
Dans le cabinet de la psychiatre Fatma Bouvet de la Maisonneuve, les patient.e.s se confient et notamment sur les discriminations auxquelles ils doivent faire face. Un miroir nous est tendu, s'y dessine notre société. Stéphane Mercurio nous restitue ces confidences et cet écho du monde.
Keywords: approches et analyses; cours; discipline; discours dominant; europe; fem3400; france; islam; médecine; premier cycle; psychiatrie; racisme; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; traumatismes; violences